Whole-body diffusion-weighted magnetic resonance imaging by estimating the measurable diffusion coefficient in Hodgkin lymphoma - A. I. Mikhaylov; V. O. Panov; I. E. Tyurin (Вестник рентгенологии и радиологии, 2016)
Objective: to determine whether the measurable diffusion coefficient (MIC) may be used to differentiate normal and lymphomatosisaltered lymph nodes (LNs) in patients with Hodgkin lymphoma (HL).Material and methods. Whole-body magnetic resonance (MR) imaging was used to compare the MICs of LNs in 27 apparently healthy  individuals and 41 patients with a verified diagnosis of HL.Results. Construction of 95% confidence intervals showed that the MICs of normal LNs were in the range of 1.00 to 1.73× ×10-3 mm2/sec and  significantly higher (p<0.05) than those of lymphomatosis-affected LNs (MIC, 0.59 to 0.94×10-3 mm2/sec). The cut-off point (for discretization) of normal and lymphomatosis-altered LNs was in the range of 0.94 to 1.00×10-3 mm2/sec. Consequently, the LN with a MIC of less than 0.94×10-3 mm2/sec may be thought of as affected by the lymphomatous process.Conclusion. MIC calculation permits differentiation of normal and affected LNs having equal signal characteristics (including those on diffusion-weighted MR images).